2023
DOI: 10.1007/s13296-023-00778-4
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Steel in the Construction Industry: Challenges and Opportunities

Alper Kanyilmaz,
Mussie Birhane,
Roy Fishwick
et al.

Abstract: The construction industry plays a critical role in tackling the challenges of climate change, carbon emissions, and resource consumption. To achieve a low-emission built environment, urgent action is required to reduce the carbon emissions associated with steel production and construction processes. Reusing structural steel elements could make a significant impact in this direction, but there are five key challenges to overcome: limited material availability, maximizing different reusable materials from demoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Extending the lifespan of steel structures in buildings can help minimise their environmental impact. Often, when steel structural members are demolished, they are recycled for new use [18]. However, reusing them instead can lead to even greater environmental benefits compared to producing new steel.…”
Section: Reused Steel Members and Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the lifespan of steel structures in buildings can help minimise their environmental impact. Often, when steel structural members are demolished, they are recycled for new use [18]. However, reusing them instead can lead to even greater environmental benefits compared to producing new steel.…”
Section: Reused Steel Members and Structuresmentioning
confidence: 99%
“…However, reusing them instead can lead to even greater environmental benefits compared to producing new steel. Therefore, longevity and environmental considerations are crucial when it comes to building with steel structures [18].…”
Section: Reused Steel Members and Structuresmentioning
confidence: 99%
“…This naturally results in a majority of Review publications, aligning with previous patterns, giving an even distribution between DfD and Reuse. The topics emphasized are LCA [21,57,[69][70][71], adaptability [21][22][23][24]57,69,70,72,73], and the potential of CE integration within specific materials like concrete [18,22,24,74], timber [23,75], and steel [73,[76][77][78][79][80], which is further explored in Section 4.5. Additionally, through the further examination of publications within the CE investigation, the recurrent critical research gaps have been identified as the need for precise standardization [21][22][23]57,74,77,78,81], digital tool integration [81], and overcoming challenges in policy [69,76,78], market acceptance [73,78], and industry-wide adoption to advance CE [18,22,72,74,…”
Section: Research Type and Circular Designmentioning
confidence: 99%
“…SC: [67] Upcycling SC: [55,56] Reuse SC: [85,96], CE: [79] CD: [61][62][63][64][65][87][88][89][90][91][92]97] CT: [20,[30][31][32]34] CD: [62,84], CE: [18,70,[73][74][75][76]78,80] CE: [98] General CE CT: [68] CT: [16] CE: [57], CT: [58,59], CD: [60] DfD and Reuse SC: [35] DfD CT: [94,95,99], CE: [71], SC: [66,[100][101][102] CD: [83,…”
Section: Deconstructionmentioning
confidence: 99%
“…However, as Ismaeel [79] pointed out, the materials with such certifications are not widely available. Limited availability is also a concern when reclaimed materials are intended to be used, and projects often struggle to find sufficient quantity and quality of reclaimed materials [49,80].…”
Section: Limited Availability Of Sustainable Materials and Technologiesmentioning
confidence: 99%